NIMG-68. IMAGING PHOSPHOLIPID BIOSYNTHESIS ENABLES NON-INVASIVE ASSESSMENT OF BRAIN TUMOR RESPONSE TO THERAPY. (14th November 2022) - Taglang, Celine; Batsios, Georgios; Tran, Meryssa; Gillepspie, Anne Marie; Viswanath, Pavithra
Abstract: Elevated phospholipid biosynthesis is a metabolic hallmark of cancer. Due to the high membrane turnover associated with uncontrolled proliferation, tumor cells invariably upregulate phospholipid biosynthesis. Choline is a dietary nutrient that is phosphorylated to phosphocholine (PC) and subsequently incorporated into phosphatidylcholine, which is the primary membrane phospholipid in mammalian cells. Choline kinase α (CKα) is the key enzyme in this pathway and its expression is elevated in most cancers. Identifying non-invasive methods of imaging CKα activity, can, therefore, enable assessment of tumor burden and response to therapy. Deuterium magnetic resonance spectroscopy (DMRS) following administration of 2 H-labeled substrates recently emerged as a simple, robust, clinically translatable method of assessing metabolic activity in vivo . The goals of the current study were to determine whether DMRS-based assessment of PC production from [ 2 H9 ]-choline tracks CKα activity and to establish the utility of [ 2 H9 ]-choline for glioma imaging in vivo . First, we show that [ 2 H9 ]-choline metabolism to PC can be observed in live patient-derived glioma cells (GBM6 and BT88). Silencing CKα abrogates PC production from [ 2 H9 ]-choline in both GBM6 and BT88 models, thereby confirming that [ 2 H9 ]-choline provides a readout of CKα activity. Next, we examined the ability of [ 2 H9 ]-choline to monitor tumor burden and response to therapy in vivo . [ 2 H9 ]-choline metabolism to PC can be observed in mice bearing orthotopic patient-derived GBM6 or BT257 tumors, but not in tumor-free healthy controls. Importantly, following treatment of mice bearing orthotopic BT257 tumors with temozolomide, which is standard of care for glioma patients, PC production from [ 2 H9 ]-choline is reduced at early timepoints when changes in tumor volume cannot be detected by anatomical imaging. Taken together, our studies, for the first time, identify [ 2 H9 ]-choline as a probe of CKα activity and highlight its ability to assess tumor burden and early response to therapy, which is a challenge in glioma imaging.